STRATEGI KOMUNIKASI PENYIARAN DALAM PROGRAM ACARA SIRAMAN ROHANI HINDU DI LPP TVRI BALI - Ni Putu Sinta Lestari; Ni Made Yuliani; I Nyoman Subagia (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2022)
Religion needs a strategy. This became a challenge for the Balinese Society in particular to understand the teachings of Hinduism. So as to achieve this, Hinduism lays out three basic frameworks, (Tatwa / Philosophy, Ethics/susila, and Ceremonies/rituals) which one with the other fills and is a unanimous unity to live and be silent in order to achieve religious goals called Jagadhita and Moksa. Spiritual water in Hinduism one of them is dharma discourse. In doing dharma discourse in the mass media such as in LPP TVRI Bali through the Hindu spiritual splash program needs to do a strategy, method, and technique to attract people to be more interested in watching the show of Hindu spiritual shingles. There is 3 issues on this topic, that is: (1). How to choose the topic for Siraman Rohani Hindu program on LPP TVRI Bali for the community. (2). How the broadcasting communication strategy for Siraman Rohani Hindu on LPP TVRI Bali. (3). What is the impact of Siraman Rohani Hindu on LPP TVRI Bali to the community. The theory that is used is Agenda Setting Theory and Dependency Effect Mass Communication theory. Data collection techniques are done by observation, interview, and documentation. Data providing technique using qualitative descriptive. This study found including the option of topic for the program, it is needed to plan and prepare competent source person and announcer in their field and deliver topics using appropriate methods and techniques. Communication broadcasting strategy is used to attract an audience by applying broadcasting strategy using sociodrama, promotion strategy through social media, and persuasive communication strategy. Evaluation in applying strategies such as evaluation of the on-air process, evaluation of resource persons, and evaluation of the production. The impact of Siraman Rohani Hindu program on society is as there is a Cognitive impact, affective impact, and behavioral impact.